Waterborne Polyurethane Treated with Flame Retardant Based on Polydimethylsiloxanes and Boron Phenolic Resin for Improving the Char Residue and Anti-Dripping Performance - Yadian Xie; Chao Liu; Yujie Wang; Dongmei Bao; Wei Yan; Guoyong Zhou (Molecules)
Waterborne polyurethane (WPU) was cured with a flame retardant composed of polydimethylsiloxanes and boron phenolic resin. In comparison to unmodified WPU, the heat resistance of the cured WPU film was significantly improved by approximately 40.0 °C, and the limited oxygen index (LOI) increased from 21.9% to 32.6%. The outcomes reveal that the char residue yield of the cured WPU reached a substantial 8.93 wt.% at 600 °C, which is 60 times that of the unmodified WPU. The flame retardant facilitates the creation of char residue with a high degree of graphitization. Furthermore, the total smoke production (TSP), average effective heat of combustion (AEHC), total heat release (THR), and peak heat release rate (pHRR) of the cured WPU were diminished by 66.29%, 48.89%, 28.01%, and 27.96%, respectively, compared to the unmodified WPU. The CO/CO2 emission ratio was elevated by 46.32%, and the total flue gas emission was cut by 66.29%, demonstrating a remarkable smoke suppression effect. The cured WPU attained the UL-94 V0 rating without melt-dripping. These results indicate that the combined flame retardants (2.0 wt.%) can endow WPU with outstanding flame retardant properties.